TEACHER VS. PEER SCAFFOLDING MODES IN L2 WRITING CLASSES: A CONSIDERATION OF GENRE APPROACH TO WRITING - Malihe Rezaei; Nasrin Shokrpour (Universitas Katolik Indonesia Atma Jaya, 2011)
While it is not a long time that scaffolding is applied in writing classes, few attempts have been made to identify the scaffolding mechanisms that teachers and peers employ in face-to-face interactions to help students develop requirements of different genres of writing. Therefore, this study was conducted aiming at investigating the scaffolding behaviors and mechanisms that the teacher and peers employed while revising two genres of writing, i.e. description and essay, written by the students of two classes who were assigned to teacher and peer scaffolding. Vygotsky's Socio-cultural framework and its related notion of scaffolding metaphor were used in this study. To identify the scaffolding behaviors, the verbal interaction between the students and the teacher and peer mediators was recorded, transcribed and coded, using Lidz's scale (1991). Based on the findings of the study, the difference between the teacher's and peers' scaffolding behaviors in the two genres of writing was significant, illustrating the fact that not only the teacher and peer mediators offered different numbers of scaffolding behaviors, but also the type of these behaviors was at times different from a particular genre of writing to another. Finally, some pedagogical implications of Socio-cultural Theory in EFL/ESL writing classes are provided. Keywords: genres approach, scaffolding, Sociocultural Theory (SCT), Zone of Proximal Development (ZPD), teacher and peer mediators, writing